Multidisciplinary preliminary design and integration of the transmission system in a pusher geared contra-rotating open rotor - San Benito Pastor, Diana Guiomar (Cranfield University, 2020)
One of the main challenges for the aviation industry is to reduce its global environmental footprint. Geared contra-rotating open rotors have the potential to further reduce fuel consumption relative to geared turbofans, but require a more- complex speed-reducing transmission system to drive the propellers. Hitherto, the preliminary design for such transmission systems has been reported independently of the overall engine modelling or has been limited by many pre- determined engine constraints. This has restricted the feasible design space of the engine and the transmission system. Therefore, this research addresses two key questions: Can the preliminary design of the transmission system be done from cycle parameters without imposing additional engine-based constraints? How does the introduction of more rigorous preliminary design processes for the transmission system affect the design space of the open rotor engine? The transmission system in the contra-rotating open rotor comprises two main components: a power gearbox and a pitch change mechanism. These technology enablers enhance engine performance by decoupling the operation of the propellers from the free power turbine and adjusting the pitch of the blades respectively. The best power gearbox option in a contra-rotating open rotor is a differential planetary gearbox, which enables contra-rotation of the output shafts and a high power transfer with a reduced size. The space envelope of the power gearbox varies with the torque ratio between its output shafts, connected to the propellers. The effect of torque ratio variation on gearbox design has been analysed in this research for equal propeller rotational speeds and different speed ratios between the output shafts. This research shows that potential torque ratios lie between 1.1 and 1.33, with the higher ratios enabling more compact gearboxes having four or five planet gears. However, for a prescribed propeller rotational speed, higher torque ratios would reduce the rotational speed of the low-pressure turbine driving the propellers and potentially reduce its efficiency. Alternatively, increasing propeller rotational speeds would result in thicker radial shafts for the pitch change mechanism connected to the propeller blades. The presence of these shafts radially traversing the engine’s gas path might contribute to the blockage of the exhaust duct. To address these issues, a preliminary design framework has been developed that combines 0D thermodynamic modelling with flow path sizing and weight estimation and enables assessing the integration effects of the transmission system on engine performance. The engine’s optimum performance design space might not be accessible due to mechanical constraints or integration interactions. Relative to a baseline design, the reduction in fuel burnt can be as high as 1% with current technology levels and 3% for future designs with entry into service by 2035. However, the potential performance gains derived from improvements in turbine design might not be achievable when the transmission system is integrated. The integration of the transmission system further reduces potential fuel burn gains to 0.6% relative to a baseline engine design. A wide range of activities for future work is opened by the methods developed in this research in both performance and mechanical development of the components in the transmission system.
Sethi, Vishal - Associate Supervisor
Keywords: torque ratio variation; gearbox design; propeller speeds; output shafts; OD thermodynamic modelling; flow path sizing